Development of EEG-based epileptic detection using artificial neural network - Azian Azamimi, Abdullah; Saufiah, Abdul Rahim; Adira, Ibrahim (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/